Therapeutic Human IgG Preparations Contain Mixture of HLA Antibodies to Native HLA Antigens and Cryptic Epitopes With Little Clinical Significance. Issue 12 (December 2018) - Mangiola, Massimo; Marrari, Marilyn; Ensor, Christopher; Spycher, Martin O.; Berger, Mel; Zeevi, Adriana
Abstract : Background: Human immunoglobulins (H-Ig) are widely used in solid organ transplantation for immunoglobulin G (IgG) replacement and for desensitization and treatment of antibody-mediated rejection. They are obtained from plasma pools and may contain HLA antibodies that can be detrimental to transplant recipients. The goal of this study was to evaluate HLA antibodies in multiple lots of 2 commercial H-Ig preparations by Luminex single-antigen bead (SAB) and cell-based crossmatch assays. Methods: Thirty lots of 2 commercial H-Ig products (CSL Behring, King of Prussia, PA) were evaluated: 6 Hizentra and 24 Privigen. All were adsorbed and diluted 1:10 before testing. HLA IgG antibodies were determined by 2 Luminex SAB kits and C1q screen for complement-binding capability. Lots were tested for the presence of antibody to denatured vs. intact class I HLA alleles using acid-treated SAB. Surrogate T and B-cell flow cytometry crossmatches (FCXM) were performed with peripheral blood lymphocytes from 2 healthy donors. Results: Twenty-two (73%) lots at 1:10 showed SAB reactivity with mean fluorescent intensity of 2000 or greater for HLA class I, 67% (20/30 lots) for class II. The reactivity pattern was similar using both SAB kits. Acid treatment revealed antibodies to denatured class I: the majority of HLA-C, half of HLA-B and few HLA-A alleles. No C1q reactivity was observed. Surrogate flow cytometry crossmatch results were positive (>150 median channel shift), but were fourfold to eightfold lower than expected. Conclusions: The H-Ig products tested consisted of low titer, non–complement-binding HLA class I and class II antibodies; most of the observed class I HLA reactivity was toward denatured HLA antigens. Abstract : Thirty-two lots from 2 different commercial preparations of IVIg contain non-complement binding DSA with a MFI greater that 2000 MFI in about 2/3 of cases, the majority of which was directed against denatured antigens.